Non-generic types of bifurcations in one-dimensional discrete dynamical - Benazic Tomé, Renato Mario (2023)
In this paper we give non-generic conditions under which a one parameter-family of real functions of real variable, exhibit bifurcation values. In particular, two types of such bifurcations are presented, Type I and Type II, which would be, respectively, the discrete analogues of the transcritical and pitchfork, bifurcations found in ordinary diﬀerential equations.